Assessment of Fracture Properties in Lime-Pumice Mortars Through the Utilization of Various Specimen Types - Eren, Erkin; Ince, Ragip (ISRES Publishing, 2026)
Linear elastic fracture mechanics (LEFM) were initially applied to cementitious materials by Kaplan in 1961, followed by Kesler and his colleagues in 1972. The latter group found that LEFM was inadequate for concrete. This limitation stems from the relatively inelastic region found in quasi-brittle materials, such as concrete mixtures, rocks, and bituminous substances, which are significantly and completely fractured in advance of the crack tip. As a result, many researchers have developed non-Hookean fracture mechanics methodologies to accurately describe fracture-dominated failures in quasi-brittle structures. In this investigation, beams and single-notch cube bending (SNCB) specimens with three distinct initial crack lengths were fabricated to ascertain the fracture parameters of lime-pumice mortars. All specimens, featuring a maximum aggregate diameter of 4 mm, were maintained wrapped in stretch film within the mold for 28 days, after which they underwent three-point bending tests. The fracture parameters of the mixtures were assessed using the modified peak load method, which was recently formulated to evaluate the fracture characteristics of TPM. © 2026, ISRES Publishing. All rights reserved.
6th International Conference on Technology, ICONTECH 2026 -- 5 February 2026 through 8 February 2026 -- Budapest -- 349269
Keywords: Fracture mechanics; Lime; Pumice; Two-parameter model